Creative Mathematical Activity and Developing Mathematical Talent Through the Praxeological Model - Zeidy Margarita Barraza-García; Avenilde Romo Vázquez; Solange Roa-Fuentes (Universidad Autónoma de Baja California, 2022)
This paper presents a theoretical model for the study of mathematical talent, grounded in the Anthropological Theory of Didactics (ATD) and the notion of creativity. This model proposes two components of creative mathematical activity: the mathematical component, which supports mathematical techniques; and the creative component, defined by four functions: producing new techniques, optimizing techniques, considering tasks from different angles, and adapting a technique. Based on the theoretical model and a reference epistemological model on infinite sequences, a learning design comprising six problem situations was developed and then implemented in an institution established to foster mathematical talent. The analysis of two tasks performed by a pair of children offers a case study that illustrates how tackling challenging tasks of the same kind, in a favorable institutional setting, makes it possible to develop mathematical talent.